A Phylogenetic and Taxonomic Study on Phellodon (Bankeraceae, Thelephorales) from China - Chang-Ge Song; Yuan-Yuan Chen; Shun Liu; Tai-Min Xu; Xiao-Lan He; Di Wang; Bao-Kai Cui (Journal of Fungi, 2022)
In this study, phylogenetic analyses of Phellodon from China were carried out based on sequences from the internal transcribed spacer (ITS) regions, the large subunit of nuclear ribosomal RNA gene (nLSU), the small subunit of nuclear ribosomal RNA gene (nSSU), the largest subunit of RNA polymerase II (RPB1), and the second largest subunit of RNA polymerase II (RPB2), combined with morphological characters of the collected specimens in China. The fruiting bodies of the specimens were used to observe their characteristics, and three new species of Phellodon are discovered. Phellodon crassipileatus is characterized by its pale brown to dark brown pileal surface, tomentose pileal margin, white spines, and the presence of clamp connections in generative hyphae of pileal surface, context, and stipe. Phellodon griseofuscus is characterized by its dark brown to black pileal surface, white to pale brown pileal margin, the presence of both simple septa and clamp connections in generative hyphae of spines, and moderately long basidia. Phellodon perchocolatus is characterized by its woody and broad pileus, brown to greyish brown pileal surface when fresh, tomentose pileal margin when young, which becomes glabrous with age, and the presence of both simple septa and clamp connections in the generative hyphae of the spines. This is the first time both single and multi-genes analysis is used in such a phylogenetic and taxonomic study on Phellodon, which can provide the basis for the phylogenetic study of the genus.